Skits, comedies and farces for teen-agers a collection of humorous one-act royalty-free plays for all occasions. - Burack, A. S. (Abraham Saul) 1908- (Plays, 1970)
A collection of twenty-eight skits and one-act plays for amateur drama groups. Includes production notes for each selection.